Aplikasi Model Adaptasi Roy pada Klien Resiko Perilaku Kekerasan dengan Penerapan Asertiveness Training di RS Dr. H. Marzoeki Mahdi Bogor: Application of Roy's Adaptation Model on High-Risk Clients with Aggressive Behavior Using Assertiveness Training at RS Dr. H. Marzoeki Mahdi Bogor - Ira Erwina (Fakultas Keperawatan Universitas Andalas, 2012)
Violence or high risk of violence is one of the positive symptoms of schizophrenia (Kaplan & Sadock, 1997). Assertiveness training can decrease violent behavior in clients with schizophrenia (Wahyuningsih, 2009). The goal of this scientific paper is to describe the nursing care for clients with a high risk of violence by using Roy’s adaptation model. Assertiveness training is done for 23 clients along with general therapy and psychoeducational therapy in Utari and Srikandi rooms from 14 February to 15 April 2011. The result of assertiveness training is very effective for 23 clients and shows improvement in preventing violent behavior. Based on the result, it is important to recommend that assertiveness training can be made a standard therapy of nursing specialists and needs to be socialized at all health services.